A smoking cessation programme for current and recent ex‐smokers following diagnosis of a potentially curable cancer. Issue 9 (16th September 2016) - Ong, J.; Plueckhahn, I.; Cruickshank, D.; Churilov, L.; Mileshkin, L.
Abstract : Background: Cancer patients who quit smoking have improved survival rates. The time of diagnosis provides a 'teachable moment' when healthcare providers can offer smoking‐cessation treatment. Aims: To assess the impact on quit rates of a tailored smoking‐cessation intervention for patients diagnosed with a potentially curable cancer. Methods: A prospective, one‐arm cohort study of current smokers and recent quitters (<30 days) who had commenced treatment for a potentially curable cancer was performed. Intervention involved an initial motivational interview, regular follow up and pharmacotherapy when appropriate. Quit rates were measured at 1, 3, 6 and 12 months by self‐reported abstinence and biochemical confirmation. The primary end point was prolonged abstinence at 12 months. Changes in quality of life parameters and distress were also assessed. Results: Seventy‐one patients were recruited, with a median age of 56 years. Forty‐one patients (58%) had a smoking‐related cancer. The prolonged abstinence rate at 12 months was 24% (95% confidence interval 14–36%). Factors associated with successful quitting included being in the preparation or action phase of readiness to change at study entry ( P = 0.012) and having complications of treatment requiring hospitalisation ( P = 0.024). Between baseline and 12 months, quitters reported improvement in self‐control ( P < 0.001) and reduced levels of distress ( P = 0.03) compared to non‐quitters. Conclusion: Patients who continue to smoke after being diagnosed with cancer require intensive support to quit. An individualised behavioural and pharmacological intervention can be successful in helping patients quit smoking, with quality of life improvements seen amongst successful quitters. Population measures to stop people starting smoking remain essential.